Journal of Cultural Economics Published in cooperation with The Association for Cultural Economics International - Cameron, Samuel; Noonan, Douglas; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Cultural economics is the application of economic analysis to all of the creative and performing arts, the heritage and cultural industries, whether publicly or privately owned. It is concerned with the economic organization of the cultural sector and with the behavior of producers, consumers and governments in that sector. The subject includes a range of approaches, mainstream and radical, neoclassical, welfare economics, public policy and institutional economics. The editors and editorial board of the Journal of Cultural Economics seek to attract the attention of the economics profession to this branch of economics, as well as those in related disciplines and arts practitioners with an interest in economic issues. The Journal of Cultural Economics publishes original papers that deal with the theoretical development of cultural economics as a subject, the application of economic analysis and econometrics to the field of culture, and with the economic aspects of cultural policy. Besides full-length papers, short papers and book reviews are also published. Officially cited as: J Cult Econ.
Keywords: Culture -- Study and teaching; Arts; Music; Microeconomics; Economic policy; Culture - Economic aspects; Cultural Economics; Microeconomics; Economic Policy; Arts; Music; Regional and Cultural Studies